Integration of TaOx-based resistive-switching element and GaAs diode - Chi, Dong Zhi (2014)
We report the integration of one selection diode and one resistive-switching memory element (1D1R) structure based on a GaAs diode on germanium-on-insulator on a Si substrate integrated with Cr/TaOx/Al memory element. The 1D1R device showed unipolar resistive-switching with an ON/OFF resistance ratio of over 102 within the voltage range 1.1 V–2.0 V. In the low resistance state, a forward-to-reverse current ratio of 60 was obtained at ±1 V.